(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
This article analyzes the development processes of pilgrimage tourism in Uzbekistan, its significance at national and international levels, and the possibilities of shaping the country’s image as a global cultural center based on cultural heritage sites. The study comprehensively covers not only the religious aspects of pilgrimage tourism but also its spiritual, educational, and economic dimensions. Additionally, the article presents practical proposals for leveraging international experience, improving infrastructure, branding, and developing in harmony with educational tourism. This research serves to widely promote Uzbekistan’s tourism potential in the international arena